2014
DOI: 10.1590/s1517-83822014005000021
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization and expression of a novel laccase gene Pclac2 from Phytophthora capsici

Abstract: Laccases are blue copper oxidases (E.C. 1.10.3.2) that catalyze the one-electron oxidation of phenolics, aromatic amines, and other electron-rich substrates with the concomitant reduction of O2 to H2O. A novel laccase gene pclac2 and its corresponding full-length cDNA were cloned and characterized from Phytophthora capsici for the first time. The 1683 bp full-length cDNA of pclac2 encoded a mature laccase protein containing 560 amino acids preceded by a signal peptide of 23 amino acids. The deduced protein seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In this study, the StLAC4 gene was successfully expressed in E. coli for the first time and the maximum activity of the purified laccase reached 127.78 U · mg −1 at a lower production cost. The results showed the optimum pH for Stlac4 is 4.0, which is similar to most of the studied fungal laccases , but the optimum temperature is 60 °C, which is significantly higher than most . If this advantage can be enhanced , it may improve the potential of Stlac4 in industrial applications.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In this study, the StLAC4 gene was successfully expressed in E. coli for the first time and the maximum activity of the purified laccase reached 127.78 U · mg −1 at a lower production cost. The results showed the optimum pH for Stlac4 is 4.0, which is similar to most of the studied fungal laccases , but the optimum temperature is 60 °C, which is significantly higher than most . If this advantage can be enhanced , it may improve the potential of Stlac4 in industrial applications.…”
Section: Discussionmentioning
confidence: 57%
“…Laccases (EC 1.10.3.2) are a group of multicopper‐containing oxidases (MCOs) which can oxidize a range of aromatic compounds such as phenols and aromatic amines . Laccases are wide‐spread in nature and over 220 species of laccases have been isolated from many sources,including plants, fungi, bacteria, and insects . Fungal laccases are the most extensively studied multicopper oxidases, and while primarily considered to be involved in lignin degradation , recent studies have shown that fungal laccases participate in fruiting body formation , pigment biosynthesis , pathogenesis, and stress defense .…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the laccases studied so far originated from fungal species and the laccase activity has been demonstrated in Basidiomycetes, Ascomycetes and Deuteromycetes [4,5]. In fungi, laccases have more diverse physiological functions such as sporulation, pigment production, fruit body formation and plant pathogenesis [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of the biological function of fungal laccases suggest that this enzyme plays an important role in fungal morphogenesis and fungal virulence ( Li et al, 2013 ). In P. capsici , pectate lyase and laccase activities are important for successful infection during plant–pathogen interactions ( Feng and Li, 2014 ; Fu et al, 2015 ). Laccases, which served as blue copper oxidases, catalyze the one-electron oxidation (e.g., aromatic amines and phenolics) and other electron-rich substrates; there also has a reduction of O 2 to H 2 O concomitantly.…”
Section: Discussionmentioning
confidence: 99%